Human-Centric Approach in Corporate Sustainability: The Changing Landscape - Nur Syuhada JASNI; Haslinda YUSOFF (Communications of International Proceedings, 2020)
Today, a growing number of corporate behaviour studies are linking between human-centric approach and corporate sustainability. However, the critical elements of the human-centric approach that contributing to greater corporate sustainability have yet to be undertaken. This paper points the key elements that are important in a human-centric approach that is accelerating the integration of corporate sustainability into strategic management. The literature review revealed that greater corporate sustainability are achieved through: (1) ethical leadership that derived from endogenous (internal) or exogenous (external) events pressures; (2) managerial autonomy that centralised sustainability commitment; (3) trained employees with skills and knowledge that also driver of innovations; and (4) utilising internal and external communication tools. The contribution of this paper provides a summary of the most critical issues that emerged in this field to improve business excellence. The basis of the human-centric movement is demanded a more structured development, hence should be addressed by further research.
Keywords: Corporate sustainability; Human-centric approach; Strategic